Antioxidant Activity and Phenolic Content of Apple Cider - Nilgün Havva Budak; Filiz Ozçelik; Zeynep Banu Güzel-Seydim (Turkish Journal of Agriculture: Food Science and Technology, 2015)
Fruit and vegetables are an important component of a healthy diet and the main antioxidant suppliers in the human diet. Consumption of foods derived from fruits and vegetables is also essential; fruit juices, ciders, wines, and vinegars also contain significant amounts of polyphenolic compounds. The aim of the study was to determine the effect maceration of antioxidant activity and phenolic content of apple cider. Red delicious apples were used to produce natural apple cider with and without inclusion of maceration. Samples were taken from fresh red apple juice, macerated samples and apple cider. Apple cider (maceration was applied) (CAM) had the highest total phenolic content, chlorogenic acid, ORAC and TEAC levels. Chlorogenic acid was the dominant phenolic substance in apple juice and cider samples and chlorogenic acid was increased with maceration process.